Pengukuran Efektivitas Pembelajaran Kewirausahaan dalam Mengembangkan Keterampilan Wirausaha di Unversitas Pendidikan Indonesia Bandung - Mirza irwanda; Amir Machmud; Endang Supardi (Universitas Muhammadiyah Enrekang, 2022)
This research is motivated by the low alleged effectiveness of entrepreneurship learning on students at the University of Indonesia Education. The purpose of this study was to determine, analyze, and measure the effectiveness of entrepreneurial learning with the variable measuring entrepreneurial competence. This research method is an explanatory survey, in which a questionnaire is used as an instrument and uses a Likert scale 1-5 with data collection techniques distributing questionnaires to 394 students of Education, University of Indonesia, Bandung. Data analysis technique using SEM. The results of the study show (1) entrepreneurial competence has a significant positive effect on learning effectiveness. (2) the effectiveness of entrepreneurship learning has a positive and significant effect on entrepreneurship skills. The conclusion of this study states that the effectiveness of entrepreneurship learning can be measured by the variable of entrepreneurial competence, and entrepreneurial skills can be achieved by increasing the effectiveness of entrepreneurial learning